A versatile immunomodulated nanoCRISPR converter augments the susceptibility and visibility of tumors to the immune system - Yingjie Li; Shiyao Zhou; Wangxian Fu; Xinchao Li; Tao Chen; Hao Le; Yangsong Xu; Yuting Tang; Peng Mi; Huile Gao; Qinjie Wu; Changyang Gong (Proceedings of the National Academy of Sciences, 2025)
Immune checkpoint blockade (ICB) has potential in alleviating cytotoxic T lymphocyte (CTL) exhaustion. However, resistance that impaired major histocompatibility complex class I (MHC-I) expression on tumors can be developed in many patients after ICB treatment, resulting in insufficient antigen presentation to CTLs. Herein, we rationally design a ver s atile and po w erful i mmunomodula t ed hierar ch ical nanoCRISPR converter (SWITCH) targeting PD-L1 and PCSK9 loci to convert the immune-resistance state of tumors with high PD-L1 and low MHC-I expression for augmenting the susceptibility and visibility of tumors to the immune system. SWITCH possesses enhanced blood circulation and tumor-targeting capacity through PEGylation, acid-triggered pH low insertion peptides (pHLIPs), and interaction of hyaluronan with CD44 receptors. With the assistance of hyaluronidase and preternatural oxidative stress within tumor cells, SWITCH undergoes enzyme-responsive disassembly, charge reversal, rapid lysosomal escape, and efficient disruption of PD-L1 and PCSK9 orderly. This dual-action mechanism simultaneously blocks PD-1/PD-L1 immunosuppression while restoring MHC-I-mediated antigen presentation, resulting in enhanced the susceptibility and visibility of tumors to the immune system. Our results demonstrate SWITCH's remarkable efficacy in suppressing primary, contralateral, and recurrent tumor growth. Taken together, our study provides an encouraging strategy for relieving tumor immune resistance and further potentiating the efficacy of ICB.